3b-6-10b-3=

Simple and best practice solution for 3b-6-10b-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3b-6-10b-3= equation:


Simplifying
3b + -6 + -10b + -3 = 0

Reorder the terms:
-6 + -3 + 3b + -10b = 0

Combine like terms: -6 + -3 = -9
-9 + 3b + -10b = 0

Combine like terms: 3b + -10b = -7b
-9 + -7b = 0

Solving
-9 + -7b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + -7b = 0 + 9

Combine like terms: -9 + 9 = 0
0 + -7b = 0 + 9
-7b = 0 + 9

Combine like terms: 0 + 9 = 9
-7b = 9

Divide each side by '-7'.
b = -1.285714286

Simplifying
b = -1.285714286

See similar equations:

| 4c-5=5c-1 | | a^2-111a-3510=0 | | 1=0.3x-0.8x-39 | | 10w-4p-6w+40p= | | 82-46= | | 5(4a+b)= | | -8x-8=17-9x | | 30v=200+10v | | 4m-15=0 | | 82-48= | | 0=9x-4(2x+5) | | 15=-15c+8 | | 5.5x+6y=37 | | 5(3a+p)= | | 8x-24-9x+16=4 | | 5x+6-3x=-3+7 | | 4p+4t=100 | | m=2000(1+.07*8) | | (2x-5)-(6-7)= | | -17.375=-1.16 | | 6x+3.2=74 | | x-2=-x+5 | | m=2000(1+.07) | | -8x-10=14-10x | | 64-x=26 | | x-8/x-2= | | 12-5u=6 | | 7b^2-53b+28=0 | | 2.7y+5=-9 | | 8x^2-10=7x^2-3x | | 0=x^2-9x+28 | | X=21-2y |

Equations solver categories